2012
DOI: 10.1136/gutjnl-2012-302239
|View full text |Cite
|
Sign up to set email alerts
|

Expression of B and T lymphocyte attenuator (BTLA) in macrophages contributes to the fulminant hepatitis caused by murine hepatitis virus strain-3

Abstract: BTLA promotes the pathogenesis of virus-induced FH by enhancing macrophage viability and function. Targeting BTLA may be a novel strategy for the treatment of FH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 29 publications
0
50
0
Order By: Relevance
“…Hobit mediates the development and retention of Trm cells and NKT cells in non-lymphoid organs and other nonbarrier tissues and may provide immediate immunological protection against re-infections. BTLA is an immunoglobulin-like molecule belonging to the B7 family, which relays inhibitory signals that suppress the immune response (23). Moreover, the interaction between BTLA and its ligand has been reported to be actively involved in the adaptive immune response (24).…”
Section: Discussionmentioning
confidence: 99%
“…Hobit mediates the development and retention of Trm cells and NKT cells in non-lymphoid organs and other nonbarrier tissues and may provide immediate immunological protection against re-infections. BTLA is an immunoglobulin-like molecule belonging to the B7 family, which relays inhibitory signals that suppress the immune response (23). Moreover, the interaction between BTLA and its ligand has been reported to be actively involved in the adaptive immune response (24).…”
Section: Discussionmentioning
confidence: 99%
“…[8,12,17,19,21,25] . A stretch of hydrophobic amino acids at N-terminus of FGL2 may serve as signal peptide for sFGL2 secretion [14] , but the mechanism whereby sFGL2 is cleaved and released outside of the host cell remains to be determined.…”
Section: Structure and Functionmentioning
confidence: 99%
“…Ning et al [57,58] demonstrated that the nucleocapsid protein of MHV3 was capable of activating transcription of mouse Fgl2 gene in vitro . Serum level of sFGL2 was shown to correlate with liver cytopathology among the mice infected by MHV3 [19] . More compelling evidence suggesting that FGL2 might contribute to pathogenesis of viral infection comes from the elegant studies by Shalev et al [27] and by Marsden et al [23] , who have demonstrated that MHV3 caused fibrin deposition and hepatocellular necrosis only in Fgl2 +/+ mice but not in Fgl2 −/− mice.…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations